Assisted Peritoneal Dialysis Implementation: A Pilot Program From a Large Dialysis Unit in Quebec - Julien Melanson; Jessica Kachmar; Louis-Philippe Laurin; Naoual Elftouh; Annie-Claire Nadeau-Fredette (Canadian Journal of Kidney Health and Disease, 2022)
Background: Kidney failure prevalence is increasing in older patients for whom dialysis initiation can be challenging. Assisted peritoneal dialysis (PD), where PD is performed with the help of a healthcare worker, can facilitate PD for frailer patients who may not be candidate otherwise. Objectives: This study aimed to assess the feasibility of implementing the first pilot assisted PD program in Quebec (Canada) and to evaluate the characteristics and outcomes of the PD cohort before and after assisted PD availability. Design: Observational retrospective cohort study. Setting and Population: All adult patients initiating PD between 2015 and 2020 in a single-center dialysis unit were included. Measurements: Incidence, characteristics, and outcomes of patients with PD were compared between (1) the “pre” (2015-2017) and the “post” assisted PD era (2018-2020) and (2) patients with assisted PD and independent PD in the more recent period. Methods: The primary outcome was peritonitis rate over the first year. Secondary outcomes included hospitalization, transfers to in-center hemodialysis (HD) and mortality. Results: Overall, 124 patients initiated PD with an annual incidence of 17 ± 3 patients during the “pre” and 24 ± 8 patients during the “post” assisted PD era ( P = .18). First-year peritonitis rate was similar over the 2 eras. Years of PD initiation and use of assisted PD were not associated with risk peritonitis (over total follow-up) after adjustment. Adjusted hazard of transfer to HD or death was higher during the “post” era (hazard ratio [HR]: 2.77; 95% confidence interval [CI]: 1.42-5.58). Seventeen patients received assisted PD including 13 (18%) of the 72 patients initiated between 2018 and 2020. Patients with assisted PD were older than those with independent PD (72 [64-84] vs. 59 [47-67], P = .006) and received assistance for 0.8 (0.4-1.5) years. When comparing assisted and independent cohorts, there were no differences in crude rates of peritonitis or hospitalization. Limitations: Single-center study with small sample size. Conclusion: This study shows the feasibility of implementing an assisted PD program, with favorable overall outcomes including similar rates of peritonitis during the first year after PD initiation.